Effect to reflux ration on separation of azeotropic mixtures in batch distillation column - Wan Norazlinda, Wan Zakaria (2010)
The purpose of this study is to investigate the effect of different reflux ratio on separation of azeotropic mixtures. The azeotropic mixtures used were Ethanol/Water, MTBE/Methanol and IPA/Water. The experimental studied were conducted using Bubble Cap Distillation with 10 numbers of stages at 1 atm. The composition of feed mixtures used were 40:60 v/v. In terms of reflux ratios it was set at 1.1, 1.2, 1.3 and 1.4. The product was collected from each experiment and analyzed using refractometer to determine its concentration. The standard curve of binary mixtures of each mixtures were used for quantifying the composition in the collecting samples. From the results obtained, best reflux ratio for Ethanol/Water is 1.1 (95.8%), 1.2 for IPA/Water ( 57.64 mol%) and 1.2 for MTBE/Methanol (47.57%). The results obtained were compared with the vapour composition of binary mixtures for ordinary distillation process which are without reflux ratio. By comparing the result with the data of the vapor composition for ordinary distillation, the best reflux ratio was determined. These binary mixtures cannot be separated completely by ordinary distillation because of closed boiling point between each component which formed the azeotrope. When two mixtures were mixed, the intermolecular attraction forces in all liquid may cause the mixture to form certain inseparable composition (where vapour and liquid composition) at equilibrium are equal. Further separation can be achieved by controlling the reflux ratio of the distillation process to improve the separation efficiency. This study verified that reflux ratio influence the efficiency of the column.